The Arabin Pessary to Prevent Preterm Birth in Women With a Twin Pregnancy and a Short Cervix: The STOPPIT 2 RCT. Issue 1 (January 2022) - Norman, Jane E.; Norrie, John; MacLennan, Graeme; Cooper, David; Whyte, Sonia; Chowdhry, Sushila; Cunningham-Burley, Sarah; Neilson, Aileen R.; Mei, Xue W.; Smith, Joel B. E.; Shennan, Andrew; Robson, Stephen C.; et al.
Abstract : (Abstracted from Health Technol Assess 2021;25:1–66) In England and Wales, approximately 16 of every 1000 women have a multiple gestation. Multiple pregnancies are associated with higher rates of stillbirth and neonatal and infant mortality, as well as child disability compared with singleton pregnancies.